(3TQM GdcGajIs - (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS GdeGdcj GdcQOj GdCSfGFj GdeUQj , CHh YeQh LeGd GdOjf GHf GdMGLH , J (B646 (3g` s
(3ChdgG (B:s
(3bGd(B: (3GdcdeI daX ohVY deYfi eaQO bhdg(B: (3daX jTed GdcdeI hZjQgG, dCfg deG jJdaX Hg ShGA hVY deYfi ChdG s
(3BNQgG (B:s
(3adG jdRe ef GYJHGQ GddGRe ddcdeI YfO YQhV MPag GYJHGQ GdLGFR YfOg YQhV GdMPa, hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3dYdg(B: (3TQM cGajI Phj GdCQH aj eYQaI cdGe GdYQH GdeSei HGdEjVGM Ydi GdcGajIHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
Keywords: (3GdfMhs